Examining temporal features of BOLD-based cerebrovascular reactivity in clinical populations - Marchena-Romero, Kayley-Jasmin; Ji, Xiang; Sommer, Rosa; Centen, Andrew; Ramirez, Joel; Poulin, Joshua M.; Mikulis, David; Thrippleton, Michael; Wardlaw, Joanna; Lim, Andrew; Black, Sandra E.; MacIntosh, Bradley J. (Frontiers in Neurology, 2023)
Conventional cerebrovascular reactivity (CVR) estimation has demonstrated that many brain diseases and/or conditions are associated with altered CVR. Despite the clinical potential of CVR, characterization of temporal features of a CVR challenge remains uncommon. This work is motivated by the need to develop CVR parameters that characterize individual temporal features of a CVR challenge. Data were collected from 54 adults and recruited based on these criteria: 1) Alzheimer’s disease diagnosis or subcortical Vascular Cognitive Impairment, 2) sleep apnea, and 3) subjective cognitive impairment concerns. We investigated signal changes in blood oxygenation level dependent (BOLD) contrast images with respect to hypercapnic and normocapnic CVR transition periods during a gas manipulation paradigm. We developed a model-free, non-parametric CVR metric after considering a range of responses through simulations to characterize BOLD signal changes that occur when transitioning from normocapnia to hypercapnia. The non-parametric CVR measure was used to examine regional differences across the insula, hippocampus, thalamus, and centrum semiovale. We also examined the BOLD signal transition from hypercapnia back to normocapnia. We found a linear association between isolated temporal features of successive CO2 challenges. Our study concluded that the transition rate from hypercapnia to normocapnia was significantly associated with the second CVR response across all regions of interest (p < 0.001), and this association was highest in the hippocampus (R2 = 0.57, p < 0.0125). This study demonstrates that it is feasible to examine individual responses associated with normocapnic and hypercapnic transition periods of a BOLD-based CVR experiment. Studying these features can provide insight on between-subject differences in CVR.